Grain processing considerations influencing starch digestion and performance of feedlot cattle - Schwandt, Erin F. (Kansas State University, 2015)
Two studies evaluated dry-rolled corn (DRC) manufacturing considerations in feedlot finishing diets. In study 1, feedlots (n = 35) participated in a survey to evaluate dry-rolled corn (DRC) processing practices, processed corn particle size distribution, and fecal starch content in finishing cattle. Average particle size of dry-processed corn, including DRC and hammermill-ground corn across all operations (n = 35) was 4,223 ± 1,265 µm with a range of 1,165 to 6,823 µm. Fecal starch content averaged 19.0 ± 6.5% with a range of 7.0 to 36.6%. Diet composition was evaluated for co-product [27.8 ± 13.4%] roughage concentration [8.9 ± 2.0%] and NDF concentration [19.3 ± 4.3%]. In study 2, cross-bred yearling steers (n = 360; initial BW = 395 ± 33.1 kg) were used to evaluate the effects of dry-rolled corn (DRC) particle size in diets containing 20% (DMB) wet distiller’s grains plus solubles (WDGS) on feedlot performance, carcass characteristics, and starch digestibility. Treatments were Coarse DRC (4,882 µm; COARSE), Medium DRC (3,760 µm; MEDIUM), Fine DRC (2,359 µm; FINE), and Steam-flaked corn (SFC, 0.35 kg/L). Final BW and ADG were not affected by treatment (P > 0.05). Dry matter intake was greater and G:F was lower (P < 0.05) for steers fed DRC vs. SFC. There was a linear decrease (P < 0.05) in DMI in the final 5 weeks on feed with decreasing DRC particle size. Fecal starch decreased (linear, P < 0.01) as DRC particle size decreased. In situ starch disappearance was lower for DRC vs SFC (P < 0.05) and increased linearly (P < 0.05) with decreasing particle size at 8 and 24-h. The final study evaluated steam-flaked corn (SFC) manufacturing practices implemented, equipment utilized, and methods used and parameters targeted to measure flake quality from commercial feedlots (n = 17). Significant variables contributing to the final multiple linear regression model using enzymatic starch availability (Enzymatic) as the dependent variable were: SFC Moisture, cooled flake density (CoolFD), throughput, roll diameter, steam cabinet temperature (Temperature), and temper time (Enzymatic = 19.4476 - (0.6927*SFCMoisture) - (2.1664*CoolFD) - (0.5060*Throughput) + (0.6281*Roll Diameter) + (0.4312*Temperature) – (0.1963*Temper Time; P < 0.15).
Keywords: cattle; dry-rolled corn; feedlot; grain processing; starch digestion; steam flaked corn; Animal Sciences (0475)